Down syndrome, aging and language: considerations for the speech-language therapy - Gaete E., Maximiliano (Revista Chilena de Fonoaudiología, 2017)
The aging phenomenon of persons with Down Syndrome has gained increasing interest among disciplines related to therapeutic work with people with intellectual disability. Speech and language therapy has contributed with a large research body aimed at establishing evaluation and intervention procedures on communications and linguistic and cognitive skills of persons with Down Syndrome, mainly in early ages and teenagers. However, the life expectancy of people with Down Syndrome has shown a gradual increase, due to the progress made in the medical and therapeutic scope and in social services, which represent new challenges for clinical exercise, considering the course of apremature and accelerated aging, where certain neurobiological conditions influence the early manifestation of neurodegenerative processes. The present paper reviews the main language characteristics of adults with Down Syndrome, considering the specificities in the aging process and its relationship with Alzheimer’s disease. Furthermore, it describes the characteristics of instruments of neuropsychological assessment that includes the valorization of the language in the adult stage, and it points out strategies of the speech and language therapy approach that are applicable to the work of language capabilities of adults with Down Syndrome. Finally, the paper addresses a shortage of research dealing with the characterization and intervention of linguistic and communicative fields among the adult population with Down Syndrome, highlighting the need to develop local studies from the speech and language therapy field given the demographic change of people with intellectual disabilities in Chile.